Bean Validation in JAXB - Valový, Marcel (2014)
Currently, there is no solution providing automatic validation of objects in the problem of solving Object-to-XML Impedance Mismatch. The author chose Java SE specification JAXB for Object-to-XML mapping and Java EE specification Bean Validation for validation of JavaBean objects. This thesis focuses on the interconnection of the two specifications and creation of a new specification Bean Validation in JAXB providing automatic validation at the object level during the process of marshalling and unmarshalling. This specification also provides means for mapping XML Restrictions and Facets to Bean Validation constraints. In this thesis author presents the design of Bean Validation in JAXB facility specification, its reference implementation, written by author, and users and programmers guide.